Costing free movement: Fear and non-transposition in the Schengen area - Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2010)
Current concern at the poor implementation of EU Justice and Home Affairs policy is understandable. JHA cooperation aims to offset the risks arising from the removal of border controls within the Schengen Area, and widespread non-transposition could render freedom of movement a dangerous luxury. It is therefore heartening that the Lisbon Treaty will improve conditions for compliance. It is not just that the treaty boosts the EU's anti-infringement powers: by increasing the roles of the Commission and Parliament in drawing up policy, the treaty should herald a liberalisation of Home Affairs cooperation that would give immigrants, employers and NGOs a greater interest in implementation. There is one rub. This liberalisation could also dilute the substance of policy. With the transposition of security standards in their current form apparently so difficult, will the member states sustain the Schengen freedoms?
Keywords: 320